2022
DOI: 10.21037/tlcr-22-148
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and recurrence patterns in patients with early stage lung cancer: a multi-state model approach

Abstract: Background: We aimed to assess whether recurrence patterns affect survival and to use a multi-state model to predict the prognosis of early stage non-small cell lung cancer in patients who underwent surgical resection.Methods: Patients with early stage non-small cell lung cancer who underwent surgical resection at two tertiary medical centers between 2010 and 2015 were retrospectively analyzed. A multi-state model was employed with one initial state (surgery), two intermediate states (locoregional recurrence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
3
4
0
Order By: Relevance
“…The mortality rate of Stage I patients is higher in older age, male patients. 24,25 The risk of white race is higher, followed by Black race, Asians and Indians, which is consistent with previous studies. 25,26 Chemotherapy is negatively related to prognostic outcome of Stage IA NSCLC patients, whereas positively correlated with that of Stage IB NSCLC patients, conforming to prior reports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mortality rate of Stage I patients is higher in older age, male patients. 24,25 The risk of white race is higher, followed by Black race, Asians and Indians, which is consistent with previous studies. 25,26 Chemotherapy is negatively related to prognostic outcome of Stage IA NSCLC patients, whereas positively correlated with that of Stage IB NSCLC patients, conforming to prior reports.…”
Section: Discussionsupporting
confidence: 92%
“…We conducted multivariate data suggesting that, as expected, tumor size was positively correlated with the risk of poor differentiation. The mortality rate of Stage I patients is higher in older age, male patients 24,25 . The risk of white race is higher, followed by Black race, Asians and Indians, which is consistent with previous studies 25,26 .…”
Section: Discussionsupporting
confidence: 89%
“…Motono et al analyzed seven postoperative patients with pleural dissemination and reported that young age and poor differentiation are risk factors for pleural dissemination [ 30 ]. Previous studies have reported that older age [ 8 ], adenocarcinoma histology [ 8 , 31 ], and higher stage [ 8 , 32 ] are associated with distant recurrence. Wu et al scored the risk of distal recurrence as smoking history, additional primary malignancy, non-anatomic resections, adenocarcinoma histology, pleural invasion, and angiolymphatic invasion and reported that intermediate- or high-risk groups had a higher frequency of distal recurrence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Male sex, older age, smoking history, low-performance status, short-term recurrence, histological presence of symptoms, and poor differentiation have been reported to be poor prognostic factors for PRS [ 3 – 6 , 8 ]. However, there is still no consensus regarding the relationship between PRS and the site of recurrence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation